High-resolution phantom of a nephron for radiation nephrotoxicity evaluation in biophysical simulations - Masoud Jabbary; Hossein Rajabi (AIMS Biophysics, 2022)
Computer simulation plays an important role in medical physics. The aim of this study was to generate an accurate model to calculate the absorbed dose at the cell level in a voxelized phantom of nephrons. In order to implement a model of kidney microdosimetry, a 3D mesh phantom of a human kidney nephron, representing a cortical nephron, was digitized to create a 3D voxelized phantom of a nephron for use in Monte Carlo simulations. The phantom was fed to GATE Monte Carlo toolkits, and simulations were performed to calculate the absorbed dose/energy from alpha and electron sources over a range of energy levels. The results were compared to the results published in literature that were derived by using a stylized phantom. The dose estimated in subunits of the voxelized and stylized phantoms showed a considerable bias (average of relative differences). The maximum difference for self-absorption was 12.5%, and up to 20% for cross-absorption. The digital phantom showed very significant differences in dose distribution among the cells in different subunits of the nephron. The results demonstrated that a small dissimilarity in the size and shape of subunits can lead to a considerable difference in the microdosimetry results. The model presented in this study offers a phantom that not only presents the realistic geometry of a nephron, which has been neglected in previous stylized models, but also one that has the capability of plotting the spatial distribution of the absorbed dose for any distribution of radiopharmaceuticals in nephron cells.